Ответ:
cosα=12/13 tgα=5/12 ctgα=12/5
Пошаговое объяснение:
sin²α+cos²α=1
cos²α=1-sin²α
cos²α=1-(5/13)²
cos²α=1-25/169
cos²α=144/169
cosα=
cosα=12/13
tgα=
tgα=(5/13)/(12/13)
tgα=5/12
ctgα=1/tgα
ctgα=1/(5/12)
ctgα=12/5
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
cosα=12/13 tgα=5/12 ctgα=12/5
Пошаговое объяснение:
sin²α+cos²α=1
cos²α=1-sin²α
cos²α=1-(5/13)²
cos²α=1-25/169
cos²α=144/169
cosα=![\sqrt{\frac{144}{169} } \sqrt{\frac{144}{169} }](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cfrac%7B144%7D%7B169%7D%20%7D)
cosα=12/13
tgα=![\frac{sina}{cosa} \frac{sina}{cosa}](https://tex.z-dn.net/?f=%5Cfrac%7Bsina%7D%7Bcosa%7D)
tgα=(5/13)/(12/13)
tgα=5/12
ctgα=1/tgα
ctgα=1/(5/12)
ctgα=12/5